PENGARUH PROMOSI DAN KUALITAS PELAYANANTERHADAP KEPUASAN PELANGGAN PADAPT ECCOMERCE CAPITAL INDONESIADI JAKARTA BARAT - Faizatul Nisa Faizatul; Andi Sopandi (YBAMB, 2024)
ABSTRACT The purpose of this research is to find out how much influence promotion has on customer satisfaction at PT Ecomerce Capital Indonesia in West Jakarta, to find out how big the influence of service quality is on customer satisfaction at PT Eccomerce Capital Indonesia in West Jakarta. and to find out how much influence promotion and service quality have on customer satisfaction at PT Ecomerce Capital Indonesia in West Jakarta